L'ordine delle parole del dialetto toscano del tardo medioevo - Szilágyi, Imre (Verbum – Analecta Neolatina, 2003)
In the present article, we examine the word order of the late medieval Toscan dialect. The analysis is based on a corpus which dates back to the end of the 15th century, the Motti e facezie del Piovano Arlotto. First, we briefly present the word order of the late medieval Romance languages. Then we focus on the word order of the late medieval Toscan dialect and we show that all the characteristics observable in the medieval Romance languages (V2 phenomena, inversion, separation of the finite and non-finite for of the verb, etc.) are to be found also in our late medieval corpus. The apparently problematic case of the V1 order is given an account compatible with the old system (even though it assumes the presence of an adverb before the subject in the base order), and this account is also confirmed by examples which contain compound verb-forms.